Cancer incidence and magnetic field exposure in industries using resistance welding in Sweden. Issue 7 (1st July 2002) - Håkansson, N; Floderus, B; Gustavsson, P; Johansen, C; Olsen, J H
Abstract : Aims: To investigate cancer incidence in workers exposed to high levels of extremely low frequency magnetic fields (ELF-MF). Methods: A cohort based on the engineering industry was established. Industries assumed to use resistance welding in production were chosen in order to increase the prevalence of high exposed subjects and to reduce the influence of confounding factors. All men and women employed in these branches during 1985–94 were selected, 537 692 men and 180 529 women. Occupation, based on census information from 1980, 1985, and 1990, was linked to a job exposure matrix on ELF-MF. Four exposure groups were used by stratifying on mean workday ELF-MF exposure, using the lowest exposure group as reference. Cancer incidence was obtained by linkage to the Swedish Cancer Registry. Results: Men in the very high exposure group showed an increased incidence of tumours of the kidney, pituitary gland, and biliary passages and liver; for these cancer sites an exposure–response relation was indicated. Women in the very high exposure group showed an increased incidence of astrocytoma I–IV, with a clear exposure–response pattern. An association was suggested in the high exposure group only, for cancer of the corpus uteri and multiple myeloma. Decreased risks in the very high exposure group among men were found for cancer of the colon and connective tissue/muscle. Conclusions: The results on cancer of the liver, kidney, and pituitary gland among men are in accordance with previous observations. Regarding brain tumours and leukaemia, the outcome for women provided further support of an association. The hypothesis of a biological mechanism involving the endocrine system was partly supported.